Electrical Transmission of Modernized Locomotives of Indepedent Traction Power - Kuchta, Jozef; Fulier, Miroslav (Communications - Scientific letters of the University of Zilina, 2001)
The contribution addresses diesel-electric power transmission of modernized locomotives for independent motor traction. It describes the approach to development; the solution of modernized locomotives with hybrid AC/DC power transmission, desiqued and realized locomotive with full AC/AC power transmission. Advantages and reasonability of modernization with an advanced transmission degree (namely as AC/AC) is confirmed by total efficiency calculation as well as by benefits in basic fuel savings, which have been carried out from the real operation.